Geotechnical investigation methods : a field guide for geotechnical engineers - Hunt, Roy E. (CRC/Taylor & Francis, 2007)
The investigation phase is the most important segment of any geotechnical study. Using the correct methods and properly interpreting the results are critical to a successful investigation. Comprising chapters from the second edition of the revered Geotechnical Engineering Investigation Handbook, Geotechnical Investigation Methods offers clear, concise, and hands-on guidance for choosing and executing a variety of field investigations. This practical guide provides an affordable alternative to larger handbooks and condenses the essential elements of a geotechnical investigation into an e.